2018
DOI: 10.3390/polym11010013
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Bifunctional Thioureas and Squaramides Grafted into Old Polymers of Intrinsic Microporosity for Novel Applications

Abstract: We have prepared different polymeric chiral bifunctional thioureas and squaramides by modification of the very well-known polymers of intrinsic microporosity (PIM), specifically PIM-1 and PIM-CO-1, to be used as recoverable organocatalysts. The installation of the chiral structures into the polymers has been done in two or three steps in high yields. The catalytic activity of the resulting materials has been proved in the stereoselective nitro-Michael addition and in a cascade process, which allows the synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…The FTIR analysis showed the reaction among the phenyl isothiocyanate and amine and hydroxyl groups on gelatin backbones ( Figure 2 a). The increased peaks of the FTIR spectrum at 3300, 3180, 1530, and 830 cm −1 related to the symmetric and asymmetric -NH, C–N, and C=S bonds were observed, respectively [ 44 , 45 , 46 ], indicating phenyl isothiocyanate was grafted on the gelatin backbones successfully. A previous study has reported that the methacrylation reaction of gelatin [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR analysis showed the reaction among the phenyl isothiocyanate and amine and hydroxyl groups on gelatin backbones ( Figure 2 a). The increased peaks of the FTIR spectrum at 3300, 3180, 1530, and 830 cm −1 related to the symmetric and asymmetric -NH, C–N, and C=S bonds were observed, respectively [ 44 , 45 , 46 ], indicating phenyl isothiocyanate was grafted on the gelatin backbones successfully. A previous study has reported that the methacrylation reaction of gelatin [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…section 3.6 for chiral PIMs). [23] PIM-1-amidoxime has been reacted with acid chloride to convert it to amidoxime ester. [81] Overall, PSMs on PIM-1 through modification of the nitrile group is a commonly used approach to introduce highly polar and hydrogen-bond forming functionalities.…”
Section: Postsynthetic Modificationsmentioning
confidence: 99%
“…Among the prepared polymeric catalysts, Cat-28 showed the best enantioselectivity in the model reaction (Scheme 60). 70 Performing organic reactions under the principles of green chemistry is interesting for both academic and industrial purposes. In this context, Dong et al have shown that the reaction of 2 with malononitrile proceeded smoothly in water at 40 °C for 12 hours without any catalyst or additive to afford functionalized 2-amino-2-chromene derivatives 174 (Scheme 61).…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…Among the prepared polymeric catalysts, Cat-28 showed the best enantioselectivity in the model reaction (Scheme 60). 70…”
Section: Reaction With Malononitrilementioning
confidence: 99%